Islamic Education Model in the New Normal Era - Rz. Ricky Satria Wiranata; Kiki Melita Andriani (STAI Terpadu Yogyakarta, 2022)
The search for Islamic education models in responding to the new normal era is an ongoing process that is perfected from day to day so that it is expected to be more mature and organized. Therefore, a quick solution is needed in responding to educational problems caused by the Covid-19 pandemic in the new normal era. This research is descriptive qualitative, namely the process of presenting data as it is descriptively sourced from primary and secondary sources. The primary data in this study were the results of interviews with the Principal of SD Al-Azhar Wonosari, while the secondary data were the results of observations and documentation as well as articles related to research. The results of this study indicate that the educational model of SD Islam Al-Azhar Wonosari in the new normal era is a combination of distance education models, home visit models and face-to-face education models. The three educational models are carried out by taking into account the principles, priorities and goals of student safety that refer to the implementation standards of the YPI Al-Azhar Health protocol in the new normal era